2019
DOI: 10.15282/jmes.13.4.2019.12.0468
|View full text |Cite
|
Sign up to set email alerts
|

A review on thermo-physical properties of bio, non-bio and hybrid nanofluids

Abstract: The pressure drop and thermal performance of various nanofluids can be affected by their thermo-physical properties. However, there are many different parameters that need to be considered when determining the thermo-physical properties of nanofluids. This paper highlights a detail reviews on the thermo-physical properties of nanofluids with different material type and effect of some process parameters (such as material type, temperature and concentration) on the thermo-physical properties of nanofluids. Four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…๐œŒ ๐‘›๐‘“ = ๐œ‘ ๐œŒ ๐‘ + (1 โˆ’ ๐œ‘)๐œŒ ๐‘“ (10) Where ๐œŒ ๐‘›๐‘“ , ๐œŒ ๐‘ , ๐œŒ ๐‘“ and ๐œ‘ are the densities of the nanofluids, nanoparticles, base fluid, and volume fraction, respectively.…”
Section: Thermophysical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…๐œŒ ๐‘›๐‘“ = ๐œ‘ ๐œŒ ๐‘ + (1 โˆ’ ๐œ‘)๐œŒ ๐‘“ (10) Where ๐œŒ ๐‘›๐‘“ , ๐œŒ ๐‘ , ๐œŒ ๐‘“ and ๐œ‘ are the densities of the nanofluids, nanoparticles, base fluid, and volume fraction, respectively.…”
Section: Thermophysical Propertiesmentioning
confidence: 99%
“…Sharifpur et al [9] also investigated the thermal conductivity of water and mango bark/water nanofluid at varying concentrations (0.1 percent, 0.5 percent, and 1.0 percent) and temperatures between 10 o C and 40 o C. Compared to water, the mango bark/water nanofluid had no appreciable thermal conductivity increase. Chen et al [10] showed that palm kernel/water-EG and mango/water nanofluids had relatively low thermal conductivities compared to non-bio nanofluids and that hybrid non-bio nanofluids had the highest thermal conductivity for low nanoparticle concentration of 0.1%.…”
Section: Introductionmentioning
confidence: 99%
“…Organic particles, such as those manufactured from rice husk or wood, on the other hand, have a lower density and a lower heat conductivity than traditional HTFs. Therefore, the concept of attempting to improve the thermal conductivity of nanofluids by adding metallic particles and reducing the viscosity of traditional HTFs by adding organic particles is an innovative one [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%